Searches for third-generation squark production in fully hadronic final states in proton-proton collisions at root s=8 TeV - (:unkn) unknown (SPRINGER, 2015)
Searches for third-generation squarks in fully hadronic final states are presented using data samples corresponding to integrated luminosities of 19.4 or 19.7 fb(-1), collected at a centre-of-mass energy of 8 TeV with the CMS detector at the LHC. Three mutually exclusive searches are presented, each optimized for a different decay topology. They include a multijet search requiring one fully reconstructed top quark, a dijet search requiring one or two jets originating from b quarks, and a monojet search. No excesses above the standard model expectations are seen, and limits are set on top and bottom squark production in the context of simplified models of supersymmetry.
Keywords: Supersymmetry; Hadron-Hadron Scattering; PARTON DISTRIBUTIONS; MEASURING MASSES; MISSING ENERGY; SUPERSYMMETRY; BREAKING; NATURALNESS; PHYSICS; MODELS